mPeriod2(Brdm1) and other single Period mutant mice have normal food anticipatory activity - Pendergast, Julie S. (Sci Rep, 2017)
Animals anticipate the timing of food availability via the food-entrainable oscillator (FEO). The anatomical location and timekeeping mechanism of the FEO are unknown. Several studies showed the circadian gene, Period 2, is critical for FEO timekeeping. However, other studies concluded that canonical circadian genes are not essential for FEO timekeeping. In this study, we re-examined the effects of the Per2 (Brdm1) mutation on food entrainment using methods that have revealed robust food anticipatory activity in other mutant lines. We examined food anticipatory activity, which is the output of the FEO, in single Period mutant mice. Single Per1, Per2, and Per3 mutant mice had robust food anticipatory activity during restricted feeding. In addition, we found that two different lines of Per2 mutant mice (ldc and Brdm1) anticipated restricted food availability. To determine if FEO timekeeping persisted in the absence of the food cue, we assessed activity during fasting. Food anticipatory (wheel-running) activity in all Period mutant mice was also robust during food deprivation. Together, our studies demonstrate that the Period genes are not necessary for the expression of food anticipatory activity.